Mosquito Diversity In Blok Ireng-Ireng And Ranu Darungan Area of Bromo Tengger Semeru National Park - Dwi Rahmawati; Nirmala Fitria Firdausi; Saiful Bahri (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2022)
Bromo Tengger Semeru National Park (TNBTS) is an area that functions as a life support, and a nature conservation area that plays an important role in maintaining the balance of the ecosystem. Mosquitoes, which are ectoparasites, can be vectors of disease in humans, so a study on the identification and diversity of mosquitoes was carried out to determine the level of distribution of mosquitoes and the possibility of transmission of disease vectors in an area. The study was conducted during January-February 2021 with the non-probability sampling method, accidental sampling and the results obtained were 19 mosquito species with a diversity index calculation of H' (2.36) for Ireng-ireng Block and H' (1.71) for Ranu Darungan which both fall into the medium category.